CATS#: A Testing Technique to Support the Specification of Test Cases for Context-Aware Software Systems - Doreste, Andréa Cristina De Souza; Travassos, Guilherme Horta (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2022: Anais do XXI Simpósio Brasileiro de Qualidade de Software, 2022)
Context-Aware Software Systems (CASS) capture the context and have their behavior affected by it. Therefore, these systems must be prepared to deal with the context and its variation. If they don’t, a failure can cause profound damage since they deal closely with the real world. Nevertheless, there is a lack of software technologies to support their testing. Thus, this work presents CATS#, a testing technique to help the specification of test cases for Context-Aware Software Systems (CASS). CATS# was applied in a project by undergraduate students. The results indicate its initial feasibility to support the specification of CASS test cases for situations not covered by conventional testing techniques.